Erosão de praia associada à evolução de esporão arenoso em Parajuru, Beberibe, Ceará - Guerra, Renan Gonçalves Pinheiro (2018)
The coastal erosion is a process normally associated with anthropogenic interventions that contribute to the unbalance of the beaches' sedimentary balance. However, the natural aspects intrinsic to this process can also produce reflections in coastal areas that presents differentiated dynamics, as the coastal segments contiguous to river mouths. This dynamic character has added some complexity when controlled by the evolution of sandy spits that are conditioned by the combination of climatic events and coastal processes. In this sense, the work carried out in the littoral between the municipalities of Beberibe and Fortim sought to elucidate the relationship between the evolutionary dynamics of the Pirangi River’s Sandy Spit and the situation of the coastal erosion in the beach of Parajuru, considering the adaptive responses of the coast. The methodology consisted in the continuous monitoring of 11 points distributed in 6.2 km of shoreline, where beach profiles were collected with sediments samples and delimitation of the present and past shoreline using remote sensing techniques (1958 – 2016). The shoreline variation rates were calculated using the Digital Shoreline Analysis System (DSAS), considering the time scale of the last half century, semiarid interval and monitoring period (2015-2016). The frontal dunes protection thresholds were also defined in relation to beach morphological responses and wave transposition regimes. The analysis of the position of the coast of Parajuru enunciated a disturbing erosive situation in all the considered intervals, with average retreat of -3,04 m / year in the last decades. The morphological support of the frontal dunes was attributed as a valuable contribution in the resilience of stretches of the coast of Parajuru in relation to erosive processes (RA>5m). The compendium of this information produced a proposal for (re) ordering the use and occupation of Parajuru, based on the categories previously established by the PDP-Beberibe. This proposal has a shown that it is possible to stimulate a coexistence between environmental protection and local socio-economic development based on tourism, community shrimp farming and fishing.